Increasing iron use efficiency by controlling emitter clogging in drip irrigation systems - Huabin Yuan; Yue Wang; Zeqiang Sun; Ning Shi; Bowen Li; Changjian Ma; Yang Xiao; Quanqi Li; Yunkai Li (Agricultural Water Management, 2023)
Iron is one of the essential elements for crop growth. Traditional iron fertilizer application method by injecting iron into soil results in low utilization efficiency of iron fertilizer and a considerable amount of iron residue in the soil. Applying iron fertilizer by drip irrigation system could effectively improve the utilization efficiency of iron fertilizer. However, emitter clogging seriously restrict this technology. Here, the effects of different types of iron fertilizers [Ferrous sulfate (FeSO4); Ferric citrate (FC-Fe); Sodium ferric ethylenediamine tetraacetate (EDTA-Fe); And no iron fertilizer (CK)] on emitters clogging were assessed. The components of emitter clogging substances were detected through X-ray Diffraction and Fourier Transform Infrared Spectrometer. The results showed that different types of iron fertilizers significantly affected emitter clogging. EDTA-Fe application significantly mitigated emitter clogging, reduced the total amount of clogging substances by 49.6% on average, and increased the emitter flow rate by 21.0%. This is due to EDTA-Fe chelated scaling cations (e.g., Ca2+) in water through its functional groups, thereby reducing the contents of calcite, monohydrate calcite and dolomite. However, FeSO4 and FC-Fe application aggravated emitter clogging, and increased the total clogging substances by 52.3% and 105.8%, respectively. Surprisingly, iron precipitation was not detected in the clogging substances. FeSO4 and FC-Fe aggravated clogging mainly by increasing the formation of particulate fouling (e.g., muscovite) and chemical precipitation (e.g., calcite). This study suggested choosing EDTA-Fe in drip irrigation systems to reduce emitter clogging. The research results are of significance for improving the utilization efficiency of iron fertilizer and promoting the application of iron fertilizer drip irrigation technology.